Soliciting children's views on other-perspectives in child mental health assessments. (April 2023) - Lester, Jessica Nina; O'Reilly, Michelle; Smoliak, Olga; Muntigl, Peter; Tseliou, Eleftheria
Child mental health assessments are complex and involve the analysis of data from multiple sources to inform treatment decisions. Question sequences are central to mental health assessments; however, little research has examined the functions of questions in child mental health interactions, particularly questions that aim to elicit information from children that might be used to inform diagnosis and treatment. In this study, we utilize a large corpus of video-recorded child mental health assessments to examine the use and function of a particular kind of wh-question—circular questions—that is, questions that seek clients' views on other family members' feelings, actions, and thoughts. Using conversation analysis, we identified three "broad" functions of circular questions in child mental health assessment. Our findings provide clinicians with clinically relevant examples for using circular questions to more fully involve children in the assessment process and acquire valuable information for diagnosis.